Incidence of and improvement in inappropriate parental behaviors of mothers with young children: a retrospective cohort study conducted in collaboration with a local government - Takehiro Arai; Aya Goto; Mitsuko Komatsu; Seiji Yasumura (BMC, 2021)
Abstract Background Inappropriate parental behaviors of mothers toward young children require further study; few epidemiological studies have utilized longitudinal analysis of region-based cohorts. This study examined the frequency of incidence of and improvements in inappropriate parental behaviors of mothers with young children and related factors. Methods Among the mothers who underwent a checkup in Fukushima City in 2017, 586 mothers with data from 4-, 18-, and 42-month-old checkups were included in analysis. In this retrospective cohort study, an anonymous database was created by transcribing and matching health checkup records with questionnaires stored at the city health center. Data were analyzed using chi-square tests and logistic regression analysis, using the SPSS Ver.20.0. Results In 28.5% of mothers, inappropriate parental behaviors were not reported in the 18-month-old data but were reported in the 42-month-old data. In 3.8%, inappropriate parental behaviors were reported in the 18-month-old data but were not reported in the 42-month-old data. The most common inappropriate parental behavior reported was "yelling at the child using emotional words" (18-month-old data, 16.2%; 42-month-old data, 39.5%). Mothers with financial difficulties were 2.19 times (95%CI: 1.13-4.26) more likely to begin inappropriate parental behaviors between 18 and 42 months. Improvements in parental behaviors were significantly higher in mothers under 30 years old (p = 0.03). Conclusions It is necessary to identify mothers with financial difficulties early and to examine how to provide childcare and financial support from a local government at the time of child health checkup.